PENGARUH SPIRONOLAKTON SEBAGAI TERAPI TAMBAHAN ACE INHIBITOR DAN/ATAU ANGIOTENSIN RECEPTOR BLOCKERS TERHADAP ALBUMINURIA PADA PENYAKIT GINJAL KRONIK PRADIALITIK STUDI KLINIS ACAK TERKONTROL BUTA GANDA - -, Yuriawantini; Suwitra, Ketu; Raka Widiana, I Gde; Sidharta Loekman, Jodi; Sudhan, Wayan; Kandarini, Yenny (journal of internal medicine; Vol. 9, No. 3 September 2008)
Recently studies suggest that aldosterone contributes to progressive kidney disease. This has raised the possibility of using aldosterone antagonist in CKD. To evaluate effects of spironolactone 25 mg/day on albuminuria in CKD patients, thirty CKD patients were enrolled in randomized double blind placebo controlled study. Permutted block randomization was done to receive spironolactone 25 mg/day or placebo as control in addition to ACE inhibitors and/or ARBs. Albuminuria and blood pressure were examined at baseline and 12 weeks. Albuminuria was measured as urinary albumin:creatinine ration and compared as primary out come. During this study 15 patient were received conventional therapy and spironolactone 25 mg/day and 15 patient were received placebo. One of patient dropped-out after 4 weeks due to hiperkalemia in spironolactone group and one of patient in the control group lost to follow-up. After 12 weeks of therapy, in spironolactone group albuminuria was decreased from 510 (180.0 ? 798.0) to 254.0 (40.3 ? 491.8) mg/g, MD, 187.0 (29.0 ? 332.3) mg/g, p= 0.035 and in control group from 804.0 (52.0 ? 1126.0) to 637.0 (99.0 ? 1098.8) mg/g MD -10.5 (-186.5-86.0) mg/g, p= 0.490. There was significant difference of decreament of albuminuria in both groups (Z=-0.69, p=0.046). There were no statistically different of serum potassium levels and blood pressure in both groups after treatment. Baseline aldosterone levels were not significantly correlated with albuminuria (r = -0.128, p = 0.499). As Conclusion in this study is spironolactone reduces albuminuria in pradialytic CKD patients
Keywords: Albuminuria, spironolactone, CKD pradialysis, ACE inhibitors, ARBs